Clinical and hematological changes in giant anteaters (Myrmecophaga tridactyla) victims of fires in the Pantanal Mato-grossense: Case report (Research, Society and Development, 2022)
The fires that happened in 2020 in the Pantanal caused intense damage to the fauna and flora of the region, and the giant anteater was one of the most affected mammals by the fires. The present study aimed to describe hematological changes found in laboratory tests of a giant anteater (Myrmecophaga tridactyla), victim of the fires that occurred in the Pantanal of Mato Grosso, correlating with the animal's clinical condition. The patient was rescued in September 2020 with serious injuries from burns in the limbs and face. After four days of hospitalization (D4), blood was collected for blood count and serum biochemistry.. A decrease in erythrocyte values was noted (0.98 x106/mm3; 2.05 – 2.67 x106/mm3), hemoglobin (4.8 g/dl; 10.6 – 12.9 g/dl) and hematocrit (16%; 35.44 – 40.1%), total white blood cell count within the normal range (16.0 x 103/mm3; 5.59 - 18.14 x 103/mm3), degenerative left shift, with presence of metamielocytes (0.7 x 103/mm3; 0 – 0 x 103/mm3), rods (5.2 x 103/mm3; 0 – 0.06 x 103/mm3) and segmented (5.1 x 103/mm3; 3.91 – 3.88 x 103/mm3) . Eosinophils (3.4 x 103/mm3; 0.08 – 1.86 x 103/mm3), monocytes (0.5 x 103/mm3; 0.01 – 0.2 x 103/mm3) and platelets (168 x 103/mm3; 52.2 – 134.4 x 103/mm3) were increased and the total plasma protein values decreased (4.2 g/dl; 7.77 – 8.42 g/dl). ALT (121 UI/L; 7.51 – 23.47 UI/L), AST (143 UI/L; 13.62 – 28.62 UI/L) and CK (13252.0 UI/L; 41.45 – 81.77 UI/L) were significantly increased and total protein decreased (4.8 g/dl; 5.49 – 6.61 g/dl). Second and third degree burns in giant anteaters cause degenerative deviation, severe anemia, hypoproteinemia and marked changes in enzymes that assess muscle damage. The impact of fires in the Pantanal of Mato Grosso in 2020 needs to be assessed, requiring the implementation of more effective public policies to combat fires.